Invasive scale insect on pomegranate – a first report from India - Mallikarjun, M H; Joshi, S; Pal, R K (Indian Horticulture, 2019)
The pest was initially observed in March 2015, on a single pomegranate plantation, with 2,000 plants, aged 5 years. Later in August 2016, it was observed on 30 plants. With time 5-10 infested plants were also recorded in neighbouring fields. L. japonica infests the bark of the branches, trunk and young shoots of its hosts with dense colonies. Heavy infestations resulted in senescence, premature leaf fall, dieback and death of individual trees. The specimens were collected and deposited in Insect Systematics Laboratory of the National Bureau of Agriculturally Important Insects, Bengaluru, for identification. It was also observed that no horticultural crops were grown in near vicinity, though groundnut and cotton crops were being cultivated from past two years.